The Implementation of Teaching English Language Based on 2013 Curriculum at Private Elementary Schools of Bukit Raya District Pekanbaru - Riefky Rahmanda; Marhamah (DISCOVERY JOURNAL, 2022)
The curriculum is made to improve education in our nation. English language education is one of it. Now a day, most schools in Indonesia use 2013 curriculum. In the 2013 curriculum, the English language is erased from the main material to additional material in elementary schools. The purpose of this study is to find how did English teachers at elementary schools of Bukit Raya district Pekanbaru implement the 2013 curriculum and what kind of difficulties faced by them. This paper is mixed research. To collect the data, the researcher followed the stages as (1) made an appointment with English teachers at Bukit Raya district Pekanbaru. (2) The researcher interviewed the English teachers in order to find teachers’ difficulties in implementing 2013 curriculum. (3) The researcher provides 10 questionnaires to answer how English teachers implemented the 2013 curriculum. After analyzing the data, it is identified that media, song and games are the main support in teaching the English language. The difficulties usually the teacher faced depends on the students it selves.